Age-associated features of mitochondrial potential (ΔΨm) changes induced by rare-earth based nanoparticles - Averchenko, K.A.; Kavok, N.S.; Klochkov, V.K.; Yefimova, S.L.; Malyukina, M.Yu.; Sedyh, O.O.; Klimov, S.A. (Functional Materials, 2015)
Age-specific effects of redox-active nanoparticles (NPs) (rare-earth orthovanadates and CeO₂) of various geometrical parameters on mitochondrial potential (ΔΨm) have been studied in isolated rat hepatocytes. It was shown that extra small (1-2 nm) CeO₂ NPs at high concentrations cause a slight decrease of ΔΨm only in the hepatocytes of 3-month-old rats. The orthovanadate NPs suppress ΔΨm in concentration-dependent manner, whereas the sensitivity of mitochondria to the lower NPs concentration is higher for 20 month-old rats. Thiol protector glutathione was shown to prevent completely NPs-induced ΔΨm decrease. For the old animals, thiol protection against the NPs as well as exogenic pro-oxidants (H₂O₂ and t-BHP) action was more expressed. ΔΨm stabilization in the presence of the NPs was observed at pro-oxidant conditions only for the young rats. It was suggested that the reduction of mitochondrial functions under effect of the orthovanadate NPs is due to increase of reactive oxygen species (ROS) production, and it had age-related character and depended on the thiol buffer system.